2023
DOI: 10.5382/econgeo.4939
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Geochemistry and Mineralogy of Tungsten with Emphasis on Mine Wastes

Abstract: Tungsten is a valuable industrial metal with limited effective substitutes for its many industrial uses. Tungsten is classified as a critical mineral by many countries, including Canada and the United States. As such, tungsten mining is expected to increase in the future, generating waste with potential as point sources of metal leaching to the environment. Concerns about the toxicity of tungsten have recently emerged, but the element is not regulated in mine waste. The geochemical behavior of tungsten is unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The study of Kazamel et al points out that the geochemical behavior of tungsten is not well studied, hindering the prediction of W leaching from ongoing and former mining operations [41] . Limited studies have examined the behavior of W in mine wastes [67] . Kazamel et al concluded that the mobility of tungsten at low temperatures is primarily controlled by pH and its adsorption behavior [41] .…”
Section: Ore Geology and W Tailings Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Kazamel et al points out that the geochemical behavior of tungsten is not well studied, hindering the prediction of W leaching from ongoing and former mining operations [41] . Limited studies have examined the behavior of W in mine wastes [67] . Kazamel et al concluded that the mobility of tungsten at low temperatures is primarily controlled by pH and its adsorption behavior [41] .…”
Section: Ore Geology and W Tailings Propertiesmentioning
confidence: 99%
“…Their research explains the limited solubility of CaWO 4 in neutral or acidic mine waters, and the mobility of the small amount of W released is governed by the presence of Fe-oxyhydroxide minerals, the stability of the depositional environment, and the transport of colloidal material in surface water. Few studies have addressed the mobility of W in mine waste [67] .…”
Section: Ore Geology and W Tailings Propertiesmentioning
confidence: 99%
“…In hydrothermal systems, W can even exceed Mo concentrations (23) . These differences in environmental abundances are likely due to several factors, including the higher reduction potential of molybdenum relative to tungsten compounds or increased likelihood of thiomolybdate formation and precipitation (2426). The VI to IV reduction potential is typically higher for Mo than for W regardless of the ligand system (27), indicating that in ecosystems with low environmental reduction potential ( E h ), Mo(VI) may be reduced to Mo(IV), while W(VI) remains oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…The VI to IV reduction potential is typically higher for Mo than for W regardless of the ligand system (27), indicating that in ecosystems with low environmental reduction potential (E h ), Mo(VI) may be reduced to Mo(IV), while W(VI) remains oxidized. Equilibrium models of tungstate and molybdate/molybdenum sulfides suggests the selective depletion of molybdate at concentrations of sulfide between ~10 uM to 1 mM, while tungsten disulfides will form only in environments with >1 mM sulfide in marine environments (24)(25)(26), suggesting that tungstate may have been more available in both the ferruginous Archean and plausible euxinic Phanerozoic marine environments than in modern day oceans. Additionally, the lower reduction potentials of W complexes compared to Mo suggest that W-pterin may be the preferred cofactor for biochemical reactions involving lower potentials, which have been hypothesized to be more common in the earliest phases of metabolic evolution (14,16).…”
Section: Introductionmentioning
confidence: 99%